Spreadsheet Use to Calculate Creatinine Clearance From Serum Creatinine - Shrewsberry, Timothy W. (J Extra Corpor Technol, 2007)
Spreadsheets may be created to include the Cockcroft-Gault Formula (CGF) for creatinine-based estimation of glomerular filtration rate. Creatinine clearance (CrCl) provides a more accurate method for perioperative risk assessment of renal function than serum creatinine. CrCl may be used to develop guidelines for renal protective management strategies during cardiopulmonary bypass. CGF uses serum creatinine, age, kilogram weight, sex, and “logical test” functions within the spreadsheet to calculate the CrCl. Implementation of spreadsheets has the potential for numerous other calculations and may provide an accurate and consistent method of clinical perfusion management.